2008
DOI: 10.1088/1742-5468/2008/04/p04026
|View full text |Cite
|
Sign up to set email alerts
|

The angle of repose of spherical grains in granular Hele–Shaw cells: a molecular dynamics study

Abstract: Abstract. We report the results of three dimensional molecular dynamic simulations on the angle of repose of a sandpile formed by pouring mono-sized cohesionless spherical grains into a granular Hele-Shaw cell. In particular, we are interested to investigate the effects of those variables which may impact significantly on pattern formation of granular mixtures in Hele-Shaw cells. The results indicate that the frictional forces influence remarkably the formation of pile on the grain level. Furthermore, We see t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…As summarized in Fig. 1(b), we find such heaps to be characterized by several new geometrical features: (i) two external angles of repose and , (ii) an internal angle of repose , and (iii) four distinct density (packing fraction) regions, A, B, C, D. This means that instead of just the familiar single angle of repose [28], heaps may in fact display two distinct angles of repose, a fact implying the existence of four characteristic density zones in the heap. As for the external and internal angles of repose, and , we showed them to be interrelated according to Eq.…”
mentioning
confidence: 78%
“…As summarized in Fig. 1(b), we find such heaps to be characterized by several new geometrical features: (i) two external angles of repose and , (ii) an internal angle of repose , and (iii) four distinct density (packing fraction) regions, A, B, C, D. This means that instead of just the familiar single angle of repose [28], heaps may in fact display two distinct angles of repose, a fact implying the existence of four characteristic density zones in the heap. As for the external and internal angles of repose, and , we showed them to be interrelated according to Eq.…”
mentioning
confidence: 78%
“…The angle of repose start from zero and reaches very soon a stable value. Previous studies have demonstrated that the angle remains constant with further insertion of grains 14 . The growth of the height of the pile H and length L (measured from the pile profile) with grain number N in a typical cell with size w = 6 is shown in fig.3.…”
Section: Saturation Of Wall Normal Stresses With Massmentioning
confidence: 90%
“…The effect of the cell thickness w on the stability of a confined sandpile has been the subject of both experimental and numerical studies [9][10][11][12][13][14] . Careful experiments and measurements reveal that the presence of front and rear walls increases greatly the angle of repose θ as well as the maximal angle of movement θ m (the maximal angle that a granular medium can reach when carefully tilted).…”
Section: Approaching To 3-d Sandpilesmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Figure 2(f), the novel geometrical properties Downloaded by [University of Miami] at 09: 21 27 December 2014 are as follows: (i) two external angles of repose α and β, (ii) an internal angle of repose γ , and (iii) four distinct density (packing fraction) regions, A, B, C, D. In other words, instead of just the familiar single angle of repose [42], heaps may in fact show two distinct angles, a fact that implies the existence of four distinct density zones in the heap. Such properties can be recognized both in the density distribution and in the distribution of the number of contacts.…”
Section: Discussionmentioning
confidence: 99%